2012
DOI: 10.1111/j.1553-2712.2012.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

The Emergency Department Action in Smoking Cessation (EDASC) Trial: Impact on Delivery of Smoking Cessation Counseling

Abstract: Objectives The focus on acute care, time pressure, and lack of resources hamper the delivery of smoking cessation interventions in the emergency department (ED). The aim of this study was to 1) determine the effect of an emergency nurse-initiated intervention on delivery of smoking cessation counseling based on the 5As framework (ask-advise-assess-assist-arrange), and 2) assess ED nurses’ and physicians’ perceptions of smoking cessation counseling. Methods The authors conducted a pre-post trial in 789 adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 75 publications
2
33
0
1
Order By: Relevance
“…910 Numerous studies have demonstrated that the ED represents a promising site for smoking cessation interventions through self-service kiosks and culturally appropriate literature, brief interventions, and referrals to outpatient treatment. 911,912 With the high prevalence of smoking-related illnesses leading to ED visits, these episodes provide outstanding “teachable moments” to encourage cessation.…”
Section: Primary Prevention In the Emergency Departmentmentioning
confidence: 99%
“…910 Numerous studies have demonstrated that the ED represents a promising site for smoking cessation interventions through self-service kiosks and culturally appropriate literature, brief interventions, and referrals to outpatient treatment. 911,912 With the high prevalence of smoking-related illnesses leading to ED visits, these episodes provide outstanding “teachable moments” to encourage cessation.…”
Section: Primary Prevention In the Emergency Departmentmentioning
confidence: 99%
“…Finalmente, se encontró que el 98.38% considera que se debe realizar educación médica continua en tabaquismo, similar a los hallazgos en otras encuestas que evalúan la necesidad de capacitación por parte del personal de salud y que revelan que más del 90% están de acuerdo con la implementación de este tipo de temas académicos (17,22,35,36); sin embargo, en Kirguistan solo el 63% de los médicos piensa que se requiere más información (37); lo cual se encuentra sustentado en que el entrenamiento a los profesionales de la salud aumentaba la asesoría con la estrategia de las 5As, sobre todo en brindar ayuda, donde el 79.1% de los médicos familiares que tenía entrenamiento en tabaquismo realizaba asesoría a los padres de niños con enfermedades respiratorias y cerca 85% de los profesionales de la salud a nivel de urgencias ofrecían ayuda y asesoría (29,38), cifra que concuerda con el hallazgo de Kats et al, que solo el 5.7% de las enfermeras y el 5.1% realizaba esta intervención antes del entrenamiento, comparado con los datos posteriores donde el 22.5% de las enfermeras y el 18.4% de los médicos realizó la intervención (39).…”
Section: Discussionunclassified
“…Katz and colleagues 31,32 successfully implemented brief counseling and referral to outpatient counseling programs in Veterans Administration hospitals and emergency departments, with modest impacts on referrals. They found that 23% of hospitalized smokers accepted referrals.…”
Section: Discussionmentioning
confidence: 99%
“…32 Smokers with an emergency department visit accepted a referral only 7% of the time. 31 A large study in primary care clinics found that less than 5% of smokers accepted a faxed referral to a state quitline. 33 In this study, acceptance rates were higher for outpatient counseling referrals (58%) and medications (43%), and 28% of patients accepted referrals for both counseling and medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation